2021
DOI: 10.1038/s41556-021-00670-5
|View full text |Cite
|
Sign up to set email alerts
|

Skin-resident immune cells actively coordinate their distribution with epidermal cells during homeostasis

Abstract: Reprints and permissions information is available at www.nature.com/reprints.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 72 publications
4
22
0
Order By: Relevance
“…Our data derived from the Lrig1 -KO model, characterized by progressive scale fusion, point to remarkably stable LC densities during interscale shrinkage and hence adaptation of the LC network to changes in scale:interscale IFE ratios. Though not directly comparable, this partly resembles the recently reported modulation of LC numbers upon alterations of KC densities in adult, non-patterned orthokeratotic ear epidermis (Park et al, 2021). These combined findings illustrate previously unrecognized dynamics of resident immune cells and their ability to adapt to changes in tissue epithelia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our data derived from the Lrig1 -KO model, characterized by progressive scale fusion, point to remarkably stable LC densities during interscale shrinkage and hence adaptation of the LC network to changes in scale:interscale IFE ratios. Though not directly comparable, this partly resembles the recently reported modulation of LC numbers upon alterations of KC densities in adult, non-patterned orthokeratotic ear epidermis (Park et al, 2021). These combined findings illustrate previously unrecognized dynamics of resident immune cells and their ability to adapt to changes in tissue epithelia.…”
Section: Discussionsupporting
confidence: 86%
“…The interfollicular epidermis (IFE) of murine ear and back-skin harbours evenly distributed immune cells (Bergstresser et al, 1980) and is largely devoid of MCs, which mostly reside in the dermis (Hirobe, 1984; Kunisada et al, 2000). In adult ear epidermis, LCs and DETCs actively maintain a non-random distribution that depends on KC density and engages LC- expressed Rac1 (Park et al, 2021), yet the molecular mechanisms how KCs control resident immune cells remain open. Tail skin instead exhibits two distinct epidermal compartments: ‘Scale’ IFE forms a spherical epidermal patch just above hair-follicle triplets and undergoes parakeratotic differentiation, characterized by lack of a granular layer and nucleated cornified layer KCs.…”
Section: Introductionmentioning
confidence: 99%
“…These cells balance self-renewal and differentiation behaviors to maintain homeostasis over the lifetime of the animal. Recent work has provided evidence of local coordination of these behaviors, where cell fates are influenced by their direct neighbors [8], but also of large-scale organization, where dynamic behaviours of diverse cell types are coordinated [15,16]. In this highly regenerative tissue, communication between stem cells is necessary to carry out this coordination at different scales.…”
Section: Introductionmentioning
confidence: 99%
“…The skin is composed of stratified epithelium with a dry surface, whereas the intestine is a simple squamous epithelium and has many nutrients on the surface which favors the microbiome ( Grice and Segre, 2011 ; Byrd et al, 2018 ; Fan and Pedersen, 2021 ). Recently, it has been shown that LCs and DETCs actively maintain their regular distribution during homeostasis ( Park et al, 2021 ). Remarkably, these immune cells recover regular distribution within a few days after local perturbation with laser ablation and after global depletion with diphtheria toxin-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that dendritic interaction is important for maintaining a regular distribution, but the underlying mechanisms remain unclear. Interestingly, depletions of one immune population do not impact the other’s patterning ( Park et al, 2021 ). These data suggest that although LCs and DETCs have a similar tiling pattern, these cells maintain the pattern independently through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%